Application and Kinetics of Ozone in Food Preservation. (4th March 2017) - Pandiselvam, R.; Sunoj, S.; Manikantan, M. R.; Kothakota, Anjineyulu; Hebbar, K. B.
ABSTRACT: Ozone is activated oxygen and it is referred to as a triatomic form of oxygen. It is a natural agent and has a broad antimicrobial property, which together with an oxidation potential, make it an attractive option for the food industry. This article focuses on the use of ozone for preservation of vegetables, fruits and fruit juices, and highlights the inactivation mechanism of microorganisms. The application of ozone in grain storage and the quality of ozone treated grains is discussed, along with the reaction kinetics of ozone in grains.